A Child with Raccoon Roundworm Meningoencephalitis: A Pathogen Emerging in your Own Backyard?. Issue 4 (2009) - Hajek, Jan; Yau, Yvonne; Kertes, Peter; Soman, Teesta; Laughlin, Suzanne; Kanani, Ronik; Kazacos, Kevin; Dangoudoubiyam, Sriveny; Opavsky, Mary Anne
Abstract : Raccoon roundworm ( Baylisascaris procyonis ) is a cause of devastating neural and ocular disease. The first documented case of raccoon roundworm encephalitis in Canada, in a seven-year-old boy who presented with severe neurological impairment, is presented. His significant recovery illustrates the importance of clinical suspicion and the benefit of early treatment.